Assessing Functional Capacity in Occupational Health: Relevance to Family Physicians - Zulver, Paul M. (1989)
The family physician is often called on to determine the work readiness of a patient after injury. This determination can be assisted by the use of a formal functional capacity evaluation, which is available as a service through private agencies and Workers' Compensation Boards. These programs can be best used with a clear understanding of the injury and return to work process, the programs available, and most importantly, the terminology used in functional capacity evaluation. The authors describe these matters, particularly as they relate to the interaction between the family physician and the Worker's Compensation Board. Increased familiarity with these concepts will promote better communication among all who attempt to reduce the disabilities of injured workers.